2022
DOI: 10.1186/s12913-022-08230-9
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale simulations to improve disaster preparedness in hospital pharmacies

Abstract: Purpose Assess whether full-scale simulation exercises improved hospital pharmacies’ disaster preparedness. Methods Swiss hospital pharmacies performed successive full-scale simulation exercises at least four months apart. An interprofessional team created two scenarios, each representing credible regional-scale disasters involving approximately fifty casualties (a major road accident and a terrorist attack). Four exercise assessors used appraisal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…This is also a case of pharmaceutical service: a recent survey has shown that European hospital pharmacies are rather poorly prepared to emergencies and disasters ( Schumacher et al, 2021 ). Fortunately, a crisis preparedness can be improved due to dedicated training ( Schumacher et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is also a case of pharmaceutical service: a recent survey has shown that European hospital pharmacies are rather poorly prepared to emergencies and disasters ( Schumacher et al, 2021 ). Fortunately, a crisis preparedness can be improved due to dedicated training ( Schumacher et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the leader and his team, must identify quickly the problem and then make decisions, implement management tools, and communicate effectively. For this purpose, dashboards can be helpful (27). In the present survey, among hospital pharmacies with a disaster management plan, the half-created paper/electronic dashboards or other management tools (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The recent study mentioned underlined also the importance of preparing and drill it. Indeed, having management plan is a precious starting point but it is not enough on its own (27). The main point is to test and train it (28).…”
Section: Discussionmentioning
confidence: 99%
“…Managgemen bencana tidak dapat terjadi dengan baik tanpa keterlibatan semua lapisan masyarakat. Kerjasama yang baik antara pemerintah, masyarakat, dan lembaga-lembaga yang terkait sangat mempengaruhi keberhasilan managemen bencana (Schumacher et al, 2022).…”
Section: Pembahasanunclassified